Impact of land-use change on soil microbial communities, organic carbon, and total nitrogen contents in Barkachha,Mirzapur District, India - Gorems, Weldesemayat; Ghoshal, Nandita (Journal of Forestry and Natural Resources, 2026)
Land-use change is a major driver of ecosystem degradation, particularly in the dry tropics, where forests are increasingly being converted into agricultural lands. This transformation not only reduces biodiversity and alters ecosystem functions but also significantly impacts soil health. This study assessed the effects of different land-use types, namely, natural forest, de- graded forest, bamboo plantation, and agricultural land, on soil microbial community com- position and biomass, and soil carbon and nitrogen contents in the dry area of Barkachha, Mirzapur District. A total of 24 composite soil samples were collected from all land use types. Soil organic carbon, total soil nitrogen, microbial biomass, and microbial community com- position were determined by the oxidation and titration method, the micro-Kjeldahl method, the fumigation and extraction method, and FAME GC-MS, respectively. The results of the study showed a significant decline in the microbial community in agricultural and degraded lands compared to natural forest (p<0.001). In agricultural and degraded lands, the microbial community and biomass decreased by 28.8% and 22%, and 54.5% and 50%, respectively. Sim- ilarly, soil organic carbon and total nitrogen contents were markedly lower in converted land uses. Among all land use patterns, the highest organic carbon (0.84±0.054%), total nitrogen (0.123±0.013%), microbial biomass carbon (570.65±35.05µg/g), microbial biomass nitrogen (84.21±3.186µg/g), basal respiration (3.64±0.064µg/g), b-glucosidase (809.68±39.7µgµg PNP g−1 dry soil h-1) and microbial community composition were found under natural forest, followed by bamboo plantation, degraded forest, and agricultural land, in decreasing order. Among mi- crobial groups, Gram-negative (G) bacteria and fungi showed similar decreasing trends across the land-use gradient, from natural forest to agricultural land. Conversely, Gram-positive (G+) bacteria showed an increasing trend along the same gradient. The higher microbial and soil chemical properties in the bamboo plantation led to faster ecosystem recovery compared to either agricultural land or degraded lands. Therefore, bamboo plantation could be used for ecosystem recovery and sustaining soil health in response to disturbance, particularly in rela- tion to land-use change in the dry tropics.